What Drives Innovation? Lessons from COVID-19 R&D - Ruchir Agarwal; Patrick Gaule (Institute of Labor Economics (IZA), 2021)
To examine the drivers of innovation, this paper studies the global R&D effort to fight the deadliest diseases and presents four results. We find: (1) global pharmaceutical R&D activity – measured by clinical trials – typically follows the 'law of diminishing efforts': i.e. the elasticity of R&D effort with respect to market size is about 1/2 in the cross-section of diseases; (2) the R&D response to COVID-19 has been a major exception to this law, with the number of COVID-19 trials being 7 to 20 times greater than that implied by its market size; (3) the aggregate short-term elasticity of science and innovation can be very large, as demonstrated by aggregate flow of clinical trials increasing by 38% in 2020, with limited crowding out of trials for non-COVID diseases; and (4) public institutions and government-led incentives were a key driver of the COVID-19 R&D effort – with public research institutions accounting for 70 percent of all COVID-19 clinical trials globally and being 10 percentage points more likely to conduct a COVID-19 trial relative to private firms. Overall, while economists are naturally in favor of market size as a driving force for innovation (i.e."if the market size is sufficiently large then innovation will happen"), our work suggests that scaling up global innovation may require a broader perspective on the drivers of innovation – including early-stage incentives, non-monetary incentives, and public institutions.
Keywords: O31; O38; J24; 330; COVID-19; innovation; market size; pharmaceutical industry